Instructional Strategies in Ecology: A Manual for Indoor-Outdoor Ecology - Lamorena, Melchora B.; Lim, Ma. Roima S. P.; Aquino, Ma. Salvacion G.; Dorado, Salvacion L.; Dela Rosa, Estrella P. (Manila City, 2001)
A practical manual designed to provide educators with effective instructional strategies for teaching ecology in both indoor and outdoor settings, emphasizing experiential and environment-based learning.
Keywords: Ecology